Efficacy Testing of Different Microbial and Insecticides against Armyworm in Dhading, Nepal - Lamichhane, Susmita; Adhikari, Prakriti; Khanal, Dristi; Bastakoti, Saurav; Dhakal, Shiv Chandra (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2023)
Available with the full text.